Nanocrystalline triple perovskite compounds A3Fe2BO9 (A = Sr, Ba; B = W, Te) with ferromagnetic and dielectric properties for triboelectric energy harvesting. (22nd February 2022) - Kojčinović, Jelena; Sahu, Manisha; Hajra, Sugato; Tatar, Dalibor; Klaser, Teodoro; Skoko, Željko; Jagličić, Zvonko; Sadrollahi, Elaheh; Litterst, Fred Jochen; Kim, Hoe Joon; Djerdj, Igor
Abstract : The preparation, characterization and application of nanocrystalline Fe-based triple perovskites as layers in triboelectric nanogenerators (TENGs). TENG devices were tested for powering a calculator and charging various capacitors. Abstract : Four iron-based triple tungstate and tellurate perovskites have been synthesized in the nanocrystalline form using a simple sol–gel citrate route: Sr3 Fe2 WO9 (SFWO ), Ba3 Fe2 WO9 (BFWO ), Sr3 Fe2 TeO9 (SFTO ), and Ba3 Fe2 TeO9 (BFTO ). Strontium-based compounds crystallize in the tetragonal space group I 4/ m, while barium-based compounds crystallize in the hexagonal space group P 63 / mmc . All compounds possess a ferromagnetic order with high values for room-temperature magnetization. The magnetic state as traced by Mössbauer spectroscopy is heterogeneously related to disorder. The compounds also possess relatively high dielectric constants (20–199.16) measured at 1 MHz and a moderate loss factor. The synthesized triple perovskite compounds were utilized in the fabrication of vertical contact mode triboelectric nanogenerators (TENGs). The working mechanism and the electrical response of the TENGs were extensively studied. The TENG device based on BFTO /Kapton triboelectric layers produces the highest output of 88 V/2.69 μA. For the first time, the surface polarity of the triple perovskite was shown using a Kelvin probe force microscopy technique (KPFM), which elucidates the positive polarity of the triboelectric layer. Furthermore, the TENG device was used to charge several capacitors and to carry out the powering of electronics that make it an excellent choice for various self-powered applications.